2009
DOI: 10.1057/jibs.2009.89
|View full text |Cite
|
Sign up to set email alerts
|

Cultural differences, convergence, and crossvergence as explanations of knowledge transfer in international acquisitions

Abstract: In spite of the proliferation of research on cultural differences in international mergers and acquisitions, we lack systematic analyses of the impact of cultural factors on knowledge transfer. In this paper, we argue that both national and organizational cultural differences and cultural integration in the form of cultural convergence and crossvergence affect knowledge transfer in acquisitions. We develop specific hypotheses concerning the nature of these effects, and test our hypotheses with data on internat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
211
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(219 citation statements)
references
References 105 publications
(234 reference statements)
6
211
1
1
Order By: Relevance
“…Heterogeneous institutional developments and environments in international alliances may imply huge knowledge gaps between foreign and local partners (Li & Scullion, 2006). Due to the beneficial diversity of practices, beliefs and values residing in and around alliance partners (Sarala & Vaara, 2010), institutional distance could be one of the potential sources of cross-border knowledge transfer. Notwithstanding, our findings indicate that institutional distance is essentially a key impediment of international knowledge acquisition because on the one hand, it raises the perceived opportunistic behaviors of the partner and on the other hand, it results in difficulties, puzzles, and causal ambiguities associated with knowledge transfer and learning, reflecting the limited access to knowledge.…”
Section: Discussion and Conclusion Theoretical Implicationsmentioning
confidence: 99%
“…Heterogeneous institutional developments and environments in international alliances may imply huge knowledge gaps between foreign and local partners (Li & Scullion, 2006). Due to the beneficial diversity of practices, beliefs and values residing in and around alliance partners (Sarala & Vaara, 2010), institutional distance could be one of the potential sources of cross-border knowledge transfer. Notwithstanding, our findings indicate that institutional distance is essentially a key impediment of international knowledge acquisition because on the one hand, it raises the perceived opportunistic behaviors of the partner and on the other hand, it results in difficulties, puzzles, and causal ambiguities associated with knowledge transfer and learning, reflecting the limited access to knowledge.…”
Section: Discussion and Conclusion Theoretical Implicationsmentioning
confidence: 99%
“…Ranft and Lord (2000) found that autonomy improved retention, which in turn increased the transfer of technological capabilities from the target to the acquirer. However, Sarala & Vaara (2010) found that greater autonomy reduced beneficial knowledge transfer.…”
Section: Structural Integrationmentioning
confidence: 97%
“…They can affect organizational members' motivational disposition to share knowledge with others (Sarala and Vaara 2010). Prior studies have found that trust can explain the level and quality of knowledge sharing (van Dijket al 2016).…”
Section: Trust and Cultural Difference In Mncsmentioning
confidence: 99%
“…Cultural differences could prevent effective communication and mutual understanding, thus undermining trust. Sarala and Vaara (2010) argue that people tend to view organizational members in a different culture as out-group members who are less trustworthy. To overcome the challenge, MNCs made efforts as revealed by studies.…”
Section: Trust and Cultural Difference In Mncsmentioning
confidence: 99%
See 1 more Smart Citation